A new species of Polyplectropus Ulmer 1905 (Trichoptera: Polycentropodidae) from Minas Gerais State, southeastern Brazil - Rocha, Isabela Cristina; Dumas, Leandro Lourenço; Nessimian, Jorge Luiz (Zootaxa, 2016)
The adult male of a new species of the genus Polyplectropus Ulmer 1905a is described and illustrated based on specimens collected in Parque Nacional da Serra da Canastra, southeastern Brazil. Polyplectropus canastra sp. nov. can be distinguished from other Polyplectropus species by the shape of sternum IX, by the thumb-like mesolateral process of each preanal appendage, by the rectangular ventral branch of each inferior appendage in ventral view, and by the curved claw-like spines of the endothecal membrane. Among all species in the P. annulicornis Group, P. canastra is the only one with a bifid dorsolateral process of each preanal appendage and bearing spinules on the distal half of the rod-like lateral branch.